Sustainability status of integrated rice-corn and beef cattle farming agriculture business in Jember regency. (November 2018) - Sulistyono, N B E; Fanani, Z; Utami, M M D
Abstract: The research was aimed to analyze the sustainability status of a particular form of integrated agriculture business system namely rice-corn pattern planting with beef cattle breeding. The selection of research location was done based on the Multistage Sampling Method, and Purpose Sampling Method. Jember Regency was selected as the research location, because information obtained from the preliminary survey shows that paddy fields with technical irrigation system were common in Jember Regency and thus several planting patterns can be used in a particular year, namely: Rice - Corn planting pattern. In addition, farmers are also used to breed cattle especially beef cattle as an additional activity to their main farming business. Data analysis was conducted using Sustainability Analysis with MDS Rap-SISPOTTA. Based on five sustainability dimensions used here namely ecological, economic, technology and infrastructure, sociocultural, as well as legal and institutional; results were obtained indicating that an integrated beef cattle and crops agriculture business system in the studied region has a sustainability index of 44.0. It indicates that the integrated agriculture business implemented is still less sustainable dimensions with the lowest index of sustainability and thus must seriously be given attention are technology and infrastructure, as well as legal and institution.